Nutriepigenetic Modulation of Hypertension Risk: A Review of the Literature - Maria Riastuti Iryaningrum; Nanny Natalia Mulyani Soetedjo; Noormarina Indraswari; Rudi Supriyadi (Indonesian Journal of Global Health Research, 2025)
This review aimed to investigate the interplay between dietary components and epigenetic modulation in the pathogenesis of hypertension. A comprehensive literature search encompassing all published primary and secondary research dating up to March 2024 was carried out on several electronic databases, including MEDLINE, EBSCO-Host, Science Direct, ProQuest, and Google Scholar. Individual genomes and dietary intake exhibit a bidirectional relationship, influencing the hypertension risk. Unhealthy dietary patterns can compromise DNA integrity through DNA methylation and histone acetylation, ultimately affecting both systolic and diastolic blood pressure. Dietary macronutrient composition (carbohydrates, lipids, and proteins) significantly alters the expression of specific microRNAs (miRNAs) known to regulate endothelial function and blood pressure homeostasis. Moreover, micronutrients (vitamin A, D, E, Zinc, Iodine, and Sodium) can exert epigenetic effects on blood pressure via receptor interactions, potentially modifying cardiovascular disease risk. Dietary imbalances in macro and micronutrients can epigenetically influence hypertension development. Addressing these deficiencies through targeted interventions may offer a complementary approach to hypertension treatment.